Tingkat Pengetahuan terkait Efek Samping Dextromethorphan Hydrobromide pada Komunitas Cosplay: Studi Deskriptif - Lalu Dea Nune Idham; Novitarini; Mia Ariasti (Universitas Bumigora, 2026)
Dextromethorphan Hydrobromide (DMP HBr) is one of the active ingredients in cough medicine, acting as an antitussive, and is widely used by the public because it is easy to obtain. Inappropriate use of the dosage can cause various side effects, such as drowsiness, dizziness, hallucinations, and the risk of abuse. This study aims to determine the level of knowledge among cosplay community members in Mataram City regarding the side effects and risks of abusing DMP HBr in cough medicine. The study used a qualitative, cross-sectional, Post-TestOnly design. Data were collected through questionnaires and interviews with 100 respondents from three cosplay communities in Mataram City, namely Banzai Mataram Japan Community, Wibufest Mataram, and Anime no Sekai Mataram. The results showed that 45% of respondents hadknowledge at the sufficient level, 23% at the good level, and 32% at the poor level. Therefore, it can be concluded that cosplay community members in Mataram City have a sufficient level of knowledge regarding the side effects and risks of abuse of DMP HBr, but further education is still needed regarding the rational and safe use of drugs.